2017
DOI: 10.1089/ars.2016.6669
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 Mediates Angiotensin II-Induced Liver Fibrosis by Activating NLRP3 Inflammasome/IL-1β Axis via Targeting Smad7 and Spry1

Abstract: Aims: Angiotensin II (AngII), a vasoconstrictive peptide of the renin–angiotensin system (RAS), promotes hepatic fibrogenesis and induces microRNA-21(mir-21) expression. Angiotensin-(1–7) [Ang-(1–7)] is a peptide of the RAS, which attenuates liver fibrosis. Recently, it was reported that the NOD-like receptor family, pyrin domain containing 3 (NLRP3) inflammasome participated in liver fibrosis. However, it remains unclear how mir-21 mediates AngII-induced NLRP3 inflammasome activation. We investigate the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 50 publications
(77 reference statements)
5
67
0
Order By: Relevance
“…For example, Ning et al . reported that circulating miR‐21 was up‐regulated in the serum of patients with liver fibrosis and was positively associated with liver fibrosis and oxidation. Loboda et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ning et al . reported that circulating miR‐21 was up‐regulated in the serum of patients with liver fibrosis and was positively associated with liver fibrosis and oxidation. Loboda et al .…”
mentioning
confidence: 99%
“…More and more studies validated that microRNA-21-5p (miR-21-5p) is implicated with infectious or inflammatory diseases. For example, Ning et al [8] reported that circulating miR-21 was up-regulated in the serum of patients with liver fibrosis and was positively associated with liver fibrosis and oxidation. Loboda et al [9] demonstrated that miR-21 plays a dynamic role in inflammatory responses and accelerates organ failure and fibrosis.…”
mentioning
confidence: 99%
“…Additionally, there is some evidence, which suggests the roles of inflammasomes in the induction of liver fibrosis and HCC. Ning and colleagues reported that microRNA-21 activates NLRP3 inflammasome and then hepatic stellate cells (HSCs) in angiotensin II dependent manner [65]. Angiotensin II and HSCs are the main responsible parameters involved in the fibrosis of the liver [66,67].…”
Section: Inflammasomes; the Crucial Inducers Of Chronic Inflammation mentioning
confidence: 99%
“…miR-21 has been shown to promote fibro genesis in muscles and various organs including heart, kidneys, lungs and liver [15]. In liver it induces fibrosis by activating hepatic stellate cells (HSC) [16]. Recently, Ning Zuo-Wei et al (2017) showed that over expression of mir-21 promotes oxidation, increases in collagen production and to have profound effect on angiotensin activation via Spry1/ERK/NF-κB, Smad7/Smad2/3/NOX4 pathways and its down regulation exerted the opposite effects [16,17].…”
Section: Mini Reviewmentioning
confidence: 99%
“…In liver it induces fibrosis by activating hepatic stellate cells (HSC) [16]. Recently, Ning Zuo-Wei et al (2017) showed that over expression of mir-21 promotes oxidation, increases in collagen production and to have profound effect on angiotensin activation via Spry1/ERK/NF-κB, Smad7/Smad2/3/NOX4 pathways and its down regulation exerted the opposite effects [16,17]. Our article in PNAS, showed the miR-21 KO mice have reduced tumorigenic activity in multistage murine skin carcinogenesis model [18], indicating down regulation of miRNA could have therapeutic role in cancer therapy [18].…”
Section: Mini Reviewmentioning
confidence: 99%